Design and implementation of voltage regulator for a power supply - Chua, Daryl Jin An (Nanyang Technological University, 2020)
Voltage regulator is an electricity regulation device that has been widely utilized in the electronics world. Due to the technology advancement of devices and the complexity of circuit designs, voltage regulator has become an essential component to regulate the unregulated input power and to produce a more desired constant output voltage. This report portrays the knowledge and learning experience obtained throughout the final year project. The learning process includes the design and implementation of several types of voltage regulator for power supply. The most used types of voltage regulators are linear regulator and switching regulator. This project mainly constituted of research, software simulation, hardware implementation and the comparing of experimental results with the simulated and theoretical results of these two types of voltage regulators. The types of linear regulators that are being explored and implemented in this project are zener shunt, transistor shunt, transistor series, fixed and variable voltage regulators. Whereas for the switching regulators, namely, buck converter (step-down voltage regulator), boost converter (step-up voltage regulator) and buck-boost converter (inverting converter). MultiSim and LTspice XVll software are used for designing and simulating the circuits to obtain the desired outputs. The software and hardware measurements are recorded accordingly in the report. Prototype is to be designed on the breadboard and soldered onto the Printed Circuit Board (PCB). The simulation measurements and the results of the breadboard and PCB will be compared and analysed.